Pleistocene coralline algal buildups on a mid-ocean rocky shore : Insights into the MIS 5e record of the Azores - Rebelo, Ana C. (2022)
Located on the northern coast of Santa Maria Island (Azores Archipelago, central North Atlantic), the Lagoinhas section preserves a carbonate buildup correlated with Marine Isotope Substage (MIS) 5e, the warmest interval of the Last Interglacial. The buildup is formed mainly by crustose coralline algae (CCA) identified as Spongites sp., and some subordinate crusts of Lithophyllum sp. and Neogoniolithon sp., as well as cf. Titanoderma sp. Extant CCA buildups are not recorded in the archipelago. Herein, we describe in detail the morphological and taphonomical features of the Lagoinhas CCA buildup and interpret the environment in which it grew. Additionally, this buildup is compared with another of similar age, exposed in the Prainha-Praia do Calhau section on the island's opposite southern coast. The hydrodynamic regime appears to play a crucial role in the development of Azorean CCA buildups during the MIS 5e.